2010
DOI: 10.1001/archneurol.2010.118
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Abnormalities and Rate of Decline in Everyday Function Across the Dementia Spectrum

Abstract: To investigate the effect of cerebrospinal fluid (CSF) abnormalities on the rate of decline in everyday function in normal aging, mild cognitive impairment (MCI), and mild Alzheimer disease (AD).Design: Immunoassays of total tau (t-tau), tau phosphorylated at threonine 181 (p-tau 181 ), and ␤-amyloid 1-42 (A␤ 42 ) concentrations were performed in CSF obtained from participants in the Alzheimer's Disease Neuroimaging Initiative. Random effects regressions were used to examine the relationship among CSF abnormal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
47
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 51 publications
7
47
1
Order By: Relevance
“…Baseline biomarker measures as a predictive factor of functional decline is a novel area of research, with very few studies having explored such relationships and of those comparable; our findings are congruent [14][15][16][41][42][43]. Two separate studies found regional cortical thinning and decreased CSF A1-42 to predict IADL decline across the AD spectrum [15,41].…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Baseline biomarker measures as a predictive factor of functional decline is a novel area of research, with very few studies having explored such relationships and of those comparable; our findings are congruent [14][15][16][41][42][43]. Two separate studies found regional cortical thinning and decreased CSF A1-42 to predict IADL decline across the AD spectrum [15,41].…”
Section: Discussionsupporting
confidence: 70%
“…Two separate studies found regional cortical thinning and decreased CSF A1-42 to predict IADL decline across the AD spectrum [15,41]. Likewise, correlations between cerebral atrophy and IADL decline in MCI individuals have been reported [14], with rate of decline found to increase three fold in APOE-4 positive individuals [42].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Numerous studies have now shown difficulties in everyday functioning to be a feature of MCI, and associated furthermore with MCI biomarkers (Ritchie et al, 2001;2010;Touchon and Ritchie, 1999;Aretouli and Brandt, 2010;Okonkwo et al, 2010a;2010b).…”
Section: What Is Impairment?mentioning
confidence: 99%
“…On the other hand, these items might be useful in combination with other items derived from similar analyses in preclinical and prodromal AD clinical trials, which consist of similar samples, as sensitive IADL outcome measures. IADL impairment in individuals across the early AD spectrum, including CN, MCI, and mild AD dementia, has been associated with multiple AD biomarkers, including measures of atrophy, hypometabolism, cortical amyloid, and cerebrospinal fluid amyloid-beta 1-42, total tau, and phospho-tau [28][29][30][31][32][33]. The current study did not include AD biomarkers in the classification of diagnoses (the classification was based solely on clinical information).…”
Section: Discussionmentioning
confidence: 99%